Effectiveness of Laparoscopic Sleeve Gastrectomy in Super-obese and Non–Super-obese Patients. Issue 5 (October 2020) - Hidalgo, Marta; Vilallonga, Ramon; Ruiz de Godejuela, Amador García; Rodríguez-Luna, María R.; Balibrea, José M.; Roriz-Silva, Renato; González, Oscar; Caubet, Enric; Ciudin, Andrea; Armengol, Manel; Fort, José M.
Abstract : Objectives: The primary aim of this study was to assess the effectiveness of sleeve gastrectomy (SG) in super-obese patients. The secondary aim was to identify patient characteristics associated with worse SG outcomes in this group. Methods: A retrospective analysis was carried out of our electronic prospective bariatric surgery patient database, including all patients who underwent SG between January 2007 and January 2017. The sample was divided according to the initial body mass index (BMI) (> or <50 kg/m 2 ). The initial characteristics and results in terms of weight loss and comorbidity resolution between the groups were compared. A subanalysis of the variable distributions was carried out according to whether or not the final BMI in the super-obese group had reached <35 kg/m 2 . Data analysis was carried out using STATA 13.1, with a P -value <0.05 considered to be significant. Results: The mean initial BMI was 42.8 kg/m 2 in group 1 (<50 kg/m 2 ) and 55 kg/m 2 in group 2 (>50 kg/m 2 ). The median follow-up (FU) was 56.2 months. Maximum weight loss was attained at the 18-month FU in both groups (BMI: 28.8 and 34.7 kg/m 2, respectively). At the 5-year FU, percentage of total weight loss was higher in group 2 and percentage of excess weight loss was statistically higher in group 1 (29.6% vs. 33.1% and 67% vs. 59%, respectively). Outcomes for type 2 diabetes mellitus, hypertension, and dyslipidemia were similar in both groups. The variables associated with attaining a final BMI <35 kg/m 2 in the super-obese group were lower initial BMI, absence of baseline weight-related conditions (type 2 diabetes mellitus, obstructive sleep apnea syndrome, home continuous positive airway pressure, arthropathy, heart disease), and absence of gastroesophageal reflux disease. Conclusions: We observed a statistically significant increase in poor outcomes in patients with a higher initial BMI and with weight-related comorbidities. These parameters could be considered to be potentially good predictors of less satisfactory outcomes in the super-obese patients.